Economic Impacts of Professional Training in the Informal Sector : The Case of the Labor Force Training Program in Côte d'Ivoire - Verner, Dorte; Verner, Mette (World Bank, Washington, DC, 2012)
The authors address the economic impact of the labor force training program (PAFPA) developed for the informal sector in Côte d'Ivoire. The data contain a subsample of the participants in the agricultural sector, tailoring sector, and the electronics sector, and a comparable control group of nonparticipants. The data have been analyzed using standard program evaluation tools, namely difference-in-difference estimators, in order to detect potential program impacts. The authors find positive economic impacts as a result of training received for some groups, namely women, the agricultural and electronics sectors, firms employing 1-3 individuals, and firms with 10 or more employees.